2018
DOI: 10.4162/nrp.2018.12.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seasonal changes on nutritional status and biochemical parameters in Turkish older adults

Abstract: BACKGROUND/OBJECTIVESAvailable data suggest that seasonal changes may influence the nutritional status and overall health of elderly individuals. Therefore, this study was conducted to investigate the effects of seasonal changes and related factors on energy and nutrient intake of older adults.SUBJECTS/METHODSIndividuals aged 65 years or over were prospectively enrolled in this single-center study (male: 11, female: 20). Data were collected between May 2013 and February 2014 during winter, spring, summer and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Considering entire populations, in climatic zones characterized by evident seasonality, dietary habits associated with a given season of the year are related to a higher supply of calories in winter and a higher intake of fats, which may result in increases of LP levels [10,11]. For instance, Ersoy et al [12] reported an increase in the consumption of high-energy food in winter months by 557 kcal daily in males and by 330 kcal in females (Turkey).…”
Section: Introductionmentioning
confidence: 99%
“…Considering entire populations, in climatic zones characterized by evident seasonality, dietary habits associated with a given season of the year are related to a higher supply of calories in winter and a higher intake of fats, which may result in increases of LP levels [10,11]. For instance, Ersoy et al [12] reported an increase in the consumption of high-energy food in winter months by 557 kcal daily in males and by 330 kcal in females (Turkey).…”
Section: Introductionmentioning
confidence: 99%
“…In any case, few studies have investigated the causes of high WC, TG, and FPG in August, so further research is needed. Furthermore, previous studies have shown that there are seasonal variations in intakes of energy, vegetable and fruit intake, and vitamin C contained in fruits and vegetables [40][41][42]. Also, because the difference between body and air temperature is slight in summer, the metabolic rate may be lower in summer than in winter.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research in Israel found that workers generally gained bodyweight and consumed over 40% more sodium chloride in the winter compared with summer [ 198 ]. Sodium intake also increased in winter in older adults in Turkey [ 199 ], in adults in Southern Brazil [ 200 ], and in a middle-aged and elderly Dutch cohort [ 201 ]. In Japanese hypertensive outpatients, 24-h urinary sodium chloride excretion, a reliable biomarker of sodium intake, generally decreased in the summer [ 202 ].…”
Section: Determinants Of Sodium Toxicitymentioning
confidence: 99%